ELECTRONIC VOTING TECHNOLOGIES IN RUSSIA - O. V. Erokhina (Publishing House of the State University of Management, 2019)
Following the global trend related to the use of digital technologies in the political process, Russia is actively introducing electronic voting technologies. Their application provides a number of advantages in the organization and conduct of elections, but also comes with risks, that require further study. An important positive effect of the introduction of Internet technologies is to increase the awareness of citizens about the elections and their participants, as well as to reduce the financial costs of voting and fast processing of its results. The main risks of the use of electronic voting technologies are associated with threats to reduce the legitimacy of elections and problems of information protection: absolute confidentiality of personal data in the framework of digital election technologies cannot be ensured, which is directly related to the technical features of electronic voting.